Organogel formation by a cholesterol-stoppered bistable [2]rotaxane and its dumbbell precursor - Zhao, Yanli (2011)
The switching properties, gelation behavior, and self-organization of a cholesterol-stoppered bistable [2]rotaxane containing a cyclobis(paraquat-p-phenylene) ring and tetrathiafulvalene/1,5-dioxynaphthalene recognition units situated in the rod portion of the dumbbell component have been investigated by electrochemical, spectroscopic, and microscopic means. The cyclobis(paraquat-p-phenylene) ring in the [2]rotaxane can be switched between the tetrathiafulvalene and 1,5-dioxynaphthalene recognition units by addressing the redox properties of the tetrathiafulvalene unit. The organogels can be prepared by dissolving the [2]rotaxane and its dumbbell precursor in a CH2Cl2/MeOH (3:2) mixed solvent and liquified by adding the oxidant Fe(ClO4)3. Direct evidence for the self-organization was obtained from AFM investigations which have shown that both of the [2]rotaxane and its dumbbell precursor form linear superstructures which we propose are helical in nature.